QUALITY AND POST-HARVEST LOSSES OF POTATO (SOLANUM TUBEROSUM L.) AS AFFECTED BY GIBBERELLIC ACID AND POTASSIUM MANAGEMENT - singh, Amanpreet (Potato Journal, 2021)
In processing industries of chip making, potato is crucial raw material for higher economic returns, so quality and storage of potato plays important role to provide superior quality product in the market. However, agronomic technologies in this crop is lacking, so modifications were made through potassium and growth regulators were made to get good results in required crop cycle Field experiments were done from 2017-18 at the Khalsa College Amritsar, Punjab, India, to assess differences due to gibberellic acid and potassium management on potato. Treatments consisted of gibberellic acid treatments: control (G1), GA3 seed application (G2) and GA3 foliar application (G3) and five potassium nutrition management treatments consisting of control (K1), 100%inorganic K (K2), 75% inorganic K+K-biofertilizer (K3), 50% inorganic K+K-biofertilizer (K4) and K-biofertilizer (K5). The GA3 treatments did not affect any quality attributes or post-harvest loss. There was an increment in processing quality with potassium nutrition treatments (K2 and K3) expect in certain quality parameters such as total phenols, ascorbic acid, total soluble solids, and chip color. Chip color lightens with application of potassium; minimum post-harvest loss occurred with K2 and K3 treatments when tubers were kept for short-term storage after harvest. At the end of the storages sprouting was decreased with potassium treatment